2020
DOI: 10.1097/mat.0000000000001283
|View full text |Cite
|
Sign up to set email alerts
|

Impella 5.5 Versus Centrimag: A Head-to-Head Comparison of Device Hemocompatibility

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 55 publications
1
31
0
Order By: Relevance
“…Previous studies support our results and showed decreased platelet surface expression of P-selectin during higher exposure to non-physiological shear stress conditions. 12,17 Geisen et al reported that 91% of LVAD patients developed an impaired degranulation of platelets, which strengthened the association of this receptor to the pathophysiology of bleeding complications. 12 A combination of this impaired platelet secretion and AVWS can lead to coagulopathies and increased spontaneous bleeding symptoms caused by dysfunctional signaling pathways that are important for platelet thrombus formation.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Previous studies support our results and showed decreased platelet surface expression of P-selectin during higher exposure to non-physiological shear stress conditions. 12,17 Geisen et al reported that 91% of LVAD patients developed an impaired degranulation of platelets, which strengthened the association of this receptor to the pathophysiology of bleeding complications. 12 A combination of this impaired platelet secretion and AVWS can lead to coagulopathies and increased spontaneous bleeding symptoms caused by dysfunctional signaling pathways that are important for platelet thrombus formation.…”
Section: Discussionmentioning
confidence: 93%
“…Pump characteristics were comparable between the two groups except for the pump speed ( P = .04), which was higher in the non‐bleeder group. Despite different rotational speeds, the tip speeds of almost all rotary blood pumps are very similar and create the same pathological shear stress on blood components 17 . Pump complications during LVAD support are listed in Table S3 in supporting information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 50 However, One in-vitro study showed that it had equivalent hemocompatibility with the CentriMag centrifugal pump. 51 The implanted HeartMate II (Thoratec Corp., Pleasanton, CA, USA) and HeartWare HVAD (HeartWare International, Inc., Framingham, MA, USA) were reported to induce more than 200 Pa of shear stress at 4.5 L/min and 80 mm Hg. 52 The latest clinical implanted HeartMate 3 (Abbott, St. Paul, MN, USA) has lower shear stress than HeartMate II and HVAD, but the artificial pulse can increase shear stress level.…”
Section: Shear Stress and Shear Rate Associated With Macmentioning
confidence: 99%
“…The World Health Organization (WHO) [ 6 ], the Extracorporeal Life Support Organization ( www.elso.org ) and others have advocated the use of extracorporeal membrane oxygenation (ECMO) for patients with severe cardiorespiratory failure. Few patients in China received ECMO support in the early phase of the pandemic and the mortality rate among these patients was high [ 7 ]. Initial experience with COVID-19 in Europe was similar as the high number of critically ill patients disrupted usual care pathways and stretched hospital resources [ 2 ].…”
mentioning
confidence: 99%